Supraorbital rim fracture caused by Intra-orbital foreign body: A case report - Anjali Wadhwa; Shweta Sharma (International Journal of Medical Research and Review, 2014)
Intra-orbital foreign bodies are more commonly seen in war injuries. Here the foreign body is normally a metallic object but when such injury occurs due to road traffic accident, the foreign body is usually organic in nature like wood. Much damage occurs to the soft tissue of the eye including globe and optic nerve but foreign body does not usually causes damage to the hard structure of eye. We are presenting a case in which a patient of road traffic accident was admitted with intra orbital foreign body of organic nature. The foreign body had not caused damage to the globe of the eye, which is more common, but has fractured the supra orbital rim of the orbit.